Kirtland Cutter : Architect in the Land of Promise - Matthews, Henry C. (Book collections on Project MUSE., 2017)
Cover -- Contents -- Preface -- Introduction -- 1 Whippoorwill Farm -- 2 The Education of an Artist -- 3 Spokane Falls: Architecture on the Frontier (1886-1889) -- 4 Cutter and Poetz: Rebuilding Downtown Spokane (1889-1891) -- 5 The Search for a Northwest Architecture (1892-1896) -- 6 Cutter and Malmgren: Mansions for Spokane's New Leaders (1897-1903) -- 7 Function and Fantasy (1898-1906) -- 8 Spokane and Seattle (1906-1909) -- 9 Summer Camps in the Wilderness (1902-1920) -- 10 The Davenport Hotel and Other Commercial Buildings (1908-1916) -- 11 Variations on an Old English Theme (1908-1920) -- 12 Mediterranean Influence (1913-1921) -- 13 Casting a Lot in Wonderland (1921-1923) -- 14 Palos Verdes and the California Style (1923-1934) -- 15 Long Beach: The Last Years (1925-1939) -- Conclusion -- Appendix 1: Cutter's Draftsmen and Partners -- Appendix 2: Cutter's Building and Projects -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y